Transportacion de terneros. II. Influencia en la morbilidad por diarrea - Alfonso, L.=700 1 Fustes, E.; Figueredo, J.M.
(Es, En)
Ilus., 12 ref.
Keywords: TERNERO; DIARREA; EDAD; TRANSPORTE DE ANIMALES; CUBA